2005
DOI: 10.1614/ws-04-169r1
|View full text |Cite
|
Sign up to set email alerts
|

Fate of acifluorfen and lactofen in common waterhemp (Amaranthus rudis) resistant to protoporphyrinogen oxidase–inhibiting herbicides

Abstract: Studies were conducted to determine acifluorfen and lactofen absorption, translocation, and metabolism in protox-inhibiting herbicide-susceptible and -resistant common waterhemp. Acifluorfen and lactofen absorption was similar in both biotypes. Herbicide absorption was 12% in both susceptible and resistant common waterhemp 6 h after treatment (HAT). Absorption increased to 32 and 42% in susceptible and resistant plants, respectively, at 72 HAT. Translocation was similar in both biotypes for both herbicides. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Shoup et al (2003) found no differences between a PPO-resistant biotype and an S-biotype of A. tuberculatus treated with acifluorfen or lactofen. Similar findings were reported by Shoup and Al-Khatib (2005) in A. tuberculatus biotypes. Price et al (2004a) reported that cotton at the 12-leaf growth stage had sevenfold greater metabolism of flumioxazin than plants at the 4- or 8-leaf growth stage.…”
Section: Resultssupporting
confidence: 91%
“…Shoup et al (2003) found no differences between a PPO-resistant biotype and an S-biotype of A. tuberculatus treated with acifluorfen or lactofen. Similar findings were reported by Shoup and Al-Khatib (2005) in A. tuberculatus biotypes. Price et al (2004a) reported that cotton at the 12-leaf growth stage had sevenfold greater metabolism of flumioxazin than plants at the 4- or 8-leaf growth stage.…”
Section: Resultssupporting
confidence: 91%
“…Of these, an altered herbicide target enzyme (PPO) was investigated, based on previous characterization of R A. tuberculatus plants (4). It was later determined, in an independently identified PPO-inhibitor-resistant A. tuberculatus population, that enhanced metabolism was not responsible for resistance (28).…”
Section: Discussionmentioning
confidence: 99%
“…Plants produced new growth within 14 DAT, and more than half of the plants in each biotype and run recovered and were actively growing at 28 DAT (unpublished data). Shoup and Al-Khatib (2005) noted similar symptoms in the first case of PPO inhibitor–resistant waterhemp reported in Kansas, but less severe final injury estimates. All three waterhemp populations were sensitive to glufosinate, glyphosate, and mesotrione, and injury estimates were 80% or higher for each (Figure 1).…”
Section: Resultsmentioning
confidence: 65%